Similar early mortality risk after cemented compared with cementless total hip arthroplasty for primary osteoarthritis: data from 188,606 surgeries in the Nordic Arthroplasty Register Association database - Pedersen AB; Mailhac A; Garland A; Overgaard S; Furnes O; Lie SA; Fenstad AM; Rogmark C; Karrholm J; Rolfson O; Haapakoski J; Eskelinen A; et al. (TAYLOR & FRANCIS LTD, 2022)
Background and purpose - Current literature indicates no difference in 90-day mortality after cemented compared with cementless total hip arthroplasty (THA). However, previous studies are hampered by potential selection bias and suboptimal adjustment for comorbidity confounding. Therefore, we examined the comorbidity-adjusted mortality up to 90 days after cemented compared with cementless THA performed due to osteoarthritis.Patients and methods - Using the Nordic Arthroplasty Register Association database, 2005-2013, we included 108,572 cemented and 80,034 cementless THA due to osteoarthritis. We calculated the Charlson comorbidity index of each patient based on data from national patient registers. The Kaplan-Meier method was used to estimate unadjusted all-cause mortality. Cox regression was used to estimate hazard ratios (HR) with 95% confidence intervals (CI) for 14, 30-, and 90-day mortality comparing cemented with cementless THA, adjusting for age, sex, comorbidity, nation, and year of surgery.Results - Cumulative all-cause mortality within 90 days was 0.41% (CI 0.37-0.46) after cemented and 0.26% (CI 0.22-0.30) after cementless THA. The adjusted HR for cemented vs. cementless fixation was 0.97 (CI 0.79-1.2), and similar risk estimates were obtained for mortality within 14 (adjusted HR 0.91 [CI 0.64-1.3]) and 30 days (adjusted HR 0.94 [CI 0.71-1.3]). We found no clinically relevant differences in mortality between cemented and cementless THA in analyses stratified by age, sex, Charlson comorbidity index, or year of surgery.Interpretation - After adjustment for comorbidity as an important confounder, we observed similar early mortality between the 2 fixation techniques.